Juvencus' presence in the prologue of the Cento Probae: A previously unnoticed case of acoustic imitation Juvencus' Präsenz im Proömium des Cento Probae: ein bisher unbemerkter Fall akustischer Imitation - Sisul, Ana Clara (Philologus, 2024)
In the prooemium of the Cento Vergilianus de Laudibus Christi of Faltonia Betitia Proba (lines 1-23) there are fragments not only of Vergil's works but also of Lucan's Bellum Civile and Juvencus' Evangeliorum Libri. This article shows that in these lines Juvencus has a particular importance, for the references to his work increase until they reach a remarkable intensity in lines 22-23 and they stand out on different levels both formally and semantically. This thesis is supported by re-examining the origin of a reference in line 22 of the Cento (erige mentem) that is usually ascribed to Lucan. The attribution to Juvencus can be established through the phenomenon of acoustic imitation.
CRIS-Team Scopus Importer:2024-06-28
Keywords: akustisch; Imitation; Juvencus; Proba